2018
DOI: 10.1097/md.0000000000013677
|View full text |Cite
|
Sign up to set email alerts
|

Modified Buzhong Yiqi decoction for myasthenia gravis

Abstract: Background:Myasthenia gravis (MG) is an autoimmune disease caused by the transmission of dysfunction in the neuromuscular junction, manifesting partial or systemic skeletal muscle weakness and fatigue, which are exacerbated by activities and relieved after rest. Currently, the conventional therapy is applying cholinesterase inhibitors, steroids, immunosuppressant, and thymectomy. However, these drugs have obvious side effects. According to traditional Chinese medicine (TCM) theory, Buzhong Yiqi decoction (BYD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In the prescription, Radix Astragali seu Hedysari is the sovereign medicinal that invigorates Qi , Radix Ginseng is the minister medicinal that powerfully tonifies the primordial Qi , nourishes the lung, and invigorates the spleen, Rhizoma Atractylodis Macrocephalae invigorates the spleen, Radix Angelicae Sinensis regulates the blood, Pericarpium Citri Reticulatae regulates Qi , and prepared Radix Glycyrrhiza helps Radix Ginseng and Radix Astragali seu Hedysari rectify Qi ; Rhizoma Cimicifugae and Radix Bupleuri have the function of eliminating pathogens and raising the clear yang. The whole formula supplements and clears in that it not only tonifies the middle and replenishes Qi , but also unblocks [13–16].…”
Section: Introductionmentioning
confidence: 99%
“…In the prescription, Radix Astragali seu Hedysari is the sovereign medicinal that invigorates Qi , Radix Ginseng is the minister medicinal that powerfully tonifies the primordial Qi , nourishes the lung, and invigorates the spleen, Rhizoma Atractylodis Macrocephalae invigorates the spleen, Radix Angelicae Sinensis regulates the blood, Pericarpium Citri Reticulatae regulates Qi , and prepared Radix Glycyrrhiza helps Radix Ginseng and Radix Astragali seu Hedysari rectify Qi ; Rhizoma Cimicifugae and Radix Bupleuri have the function of eliminating pathogens and raising the clear yang. The whole formula supplements and clears in that it not only tonifies the middle and replenishes Qi , but also unblocks [13–16].…”
Section: Introductionmentioning
confidence: 99%
“…Buzhong Yiqi Decoction is a famous prescription in ancient China that has been used for more than 700 years in China and has been widely used in the sinking of qi due to qi deficiency. [ 24 , 25 ] The composition of Buzhong Yiqi Decoction is Radix Astragali (Zhi Huang Qi), ginseng (Ren Shen), angelica sinensis (Dang Gui), tangerine peel (Chen Pi), cimicifuga foetida (Sheng Ma), bupleurum (Chai Hu), fried atractylodes (Chao Bai Zhu), and baked licorice (Zhi Gan Cao). The astragalus (Huang Qi) in this prescription could strengthen the center and benefit vital energy, raise yang and lift prolapsed zang-fu organs; Ginseng (Ren Shen), atractylodes (Bai Zhu), and glycyrrhiza (Gan Cao) could reinforce the spleen to replenish qi; tangerine peel (Chen Pi) could regulate the functional activities of qi; angelica sinensis (Dang Gui) could enrich the blood and invigorate the circulation of blood; cimicifuga foetida (Sheng Ma) and bupleurum (Chai Hu) could ascend up the spleen qi.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that using TCM combined with western medicine might improve the total effect and reduce the risk of MG relapse [ 9 ]. According to the TCM characteristic theory of “spleen governing muscle,” MG is generally diagnosed as “spleen qi deficiency syndrome” and thereby, strengthening the spleen and replenishing qi is a common therapeutic strategy of MG in TCM, which has played a positive role in clinical practice of MG [ 10 , 11 ]. Buzhong Yiqi decoction (BYD), a classical qi -supplementing formula in TCM, is the most frequently used prescription to treat MG. A study showed that BYD modulated the balance of Treg and Th17 cells in patients with MG and downregulated the serum AChR antibody level [ 12 ].…”
Section: Introductionmentioning
confidence: 99%